2022
DOI: 10.1097/jcma.0000000000000770
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of infrared ear temperature with nasopharyngeal temperature and diagnostic performance on hypothermia in general anesthetized patients

Abstract: Background: Infrared ear thermometry is widely used in clinical practice due to its noninvasive, convenient, and quick sampling. However, its accuracy and feasibility in anesthetized patients have not yet been established. Methods: We conducted this cross-sectional study to evaluate the agreement between infrared ear temperature and nasopharyngeal temperature in general anesthetized patients and its performance in intraoperative hypothermia, defined as nasopharyngeal temperature <36°C. Adult female patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Therefore, we speculate that the on-site and pre-hospital cooling could significantly shorten the duration of overheating and offer a greater benefit for patients with HS. Studies have shown that field cooling, such as cold water immersion and cold showers, can rapidly reduce the core BT and greatly reduce EHS mortality [ 14 , 37 , 38 ]; however, whether field cooling could provide the same benefits to CHS is still unknown. As presented in the Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that the on-site and pre-hospital cooling could significantly shorten the duration of overheating and offer a greater benefit for patients with HS. Studies have shown that field cooling, such as cold water immersion and cold showers, can rapidly reduce the core BT and greatly reduce EHS mortality [ 14 , 37 , 38 ]; however, whether field cooling could provide the same benefits to CHS is still unknown. As presented in the Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%